PENGARUH CITRA MEREK, PROMOSI, PERSEPSI HARGA DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN (Studi Pada Rumah Brownies Maylisa) - Anita Styaningrum (BBM (Buletin Bisnis & Manajemen), 2019)
This research is motivated by the continued decline in the number of consumers who buyand consume Brownies Maylisa Semarang since 2016 till 2018. The problem in thisresearch is what is the factor that influence a person to consumers who buy andconsume Brownies Maylisa Semarang. This specifically refers to four variables namelybrand image, promotion, price perception and location. The purpose of this study was toexamine the influence of these four variables influence purchasing decision at RumahBrownies Maylisa Semarang.The sample in this study were 96 consumers who buy and consume BrowniesMaylisa which was selected based on purposive sampling, data collection using aquestionnaires, the method used is by using multiple linier regression analysis.The results of the analysis using the t test can be seen that the variables of brandimage, promotion, price perception dan location have a significant effect on thedecisions to consumers who buy and consume at Rumah Brownies Maylisa Semarang.The Coefficient of Determination (R2) states that 59,4% of the purchasing decisions canbe influenced by brand image, promotion, price perception and location and theremaining 40,6% of the purchasing decisions is influenced by others variables.